Isa Almasih, Wafat dan Kebangkitannya (Gagasan Kristologi Islam) - Syafa’atun Almirzanah (Al-Jami'ah: Journal of Islamic Studies, 1999)
The death of Jesus Christ and his raise have been sensitive and debatable themes of discussion among followers of Christianity and Islam. This is because both Bible and Al-Qur'an do provide several verses mentioning the disputed affairs. Al-Qur'an Considers Jesus as a respectable prophet and is endowed special quality. This special view of lslam, however, does not transfer him from his humanity to divinity. Jesus is a human and God's messenger. Al-Qur'an also speaks about Jesus' death, though in aquite ambiguous manner. According to the writer, when Al-Qur'an explains about above matter it does not speak about historical event concerning his death. Rather, it shows God's superiority over the Jew's plan and claim on their success to crucify Jesus. With regard to Jesus' raise, Al-Qur'an says, according to the writer's interpretation, that ie raise must be understood as the same idea as the victory of the Muslims over the unbelievers in Badar Battle. If does not mean that Jesus physically raise and bring salvation to mankind. The victory gained by Jesus and Muhammad signifies God's approval to believers.